Urodynamic characterization in children with lower urinary tract symptoms and comorbid ADHD: a retrospective matched case-control study - Bai, Ping; Liu, Lili; Luo, Diyi (Frontiers in Pediatrics, 2026)
BackgroundLower urinary tract symptoms (LUTS) are common functional urinary disorders in children and can markedly impair quality of life. Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental condition, and emerging evidence suggests that affected children are at increased risk of LUTS. Nevertheless, systematic investigations into the relationship between ADHD and urodynamic characteristics in pediatric LUTS remain limited. This study aimed to evaluate the association between ADHD and urodynamic features in children with LUTS using a case–control design.MethodsWe conducted a retrospective case–control study including 144 children with LUTS, of whom 36 were diagnosed with ADHD. All participants underwent standardized urodynamic testing, with assessments of bladder capacity, detrusor pressure at maximum filling, and detrusor overactivity (DO). Children were categorized into ADHD and non-ADHD groups, and intergroup comparisons of urodynamic parameters were performed. Multivariable regression analysis was used to assess the independent association between ADHD and urodynamic abnormalities.ResultsCompared with the non-ADHD group (n = 108), children with ADHD (n = 36) exhibited significantly reduced volumes at first urge, strong urge, and maximum cystometric capacity (all p < 0.05). Conversely, detrusor pressure at maximum filling and the prevalence of DO were significantly higher in the ADHD group (both p < 0.05). Multivariable regression analysis identified DO as an independent predictor of urodynamic abnormalities in children with ADHD (OR = 3.43, 95% CI: 1.32–8.91, p = 0.012).ConclusionsChildren with ADHD display significant functional bladder abnormalities on urodynamic testing, particularly reduced bladder capacity, increased detrusor pressure during filling, and heightened detrusor activity. ADHD may influence bladder function, at least in part, through neurobehavioral mechanisms. These findings provide valuable clinical insights for the management of LUTS in children with ADHD and underscore the importance of early screening and intervention. Further research is needed to elucidate the underlying mechanisms and to develop effective therapeutic strategies.